Impact of manipulation of glycerol/diol dehydratase activity on intestinal microbiota ecology and metabolism. (15th March 2021) - Ramirez Garcia, Alejandro; Zhang, Jianbo; Greppi, Anna; Constancias, Florentin; Wortmann, Esther; Wandres, Muriel; Hurley, Katherine; Pascual‐García, Alberto; Ruscheweyh, Hans‐Joachim; Sturla, Shana J.; Lacroix, Christophe; Schwab, Clarissa
Summary: Glycerol/diol dehydratases (GDH) are enzymes that catalyse the production of propionate from 1, 2‐propanediol, and acrolein from glycerol. Acrolein reacts with dietary carcinogenic heterocyclic amines (HCA), reducing HCA mutagenicity, but is itself also an antimicrobial agent and toxicant. Gut microbial GDH activity has been suggested as an endogenous acrolein source; however, there is limited information on the potential of the intestinal microbiota to have GDH activity, and what impact it can have on the intestinal ecosystem and host health. We hypothesized that GDH activity of gut microbiota is determined by the abundance and distribution of GDH‐active taxa and can be enhanced by supplementation of the GDH active Anaerobutyricum hallii, and tested this hypothesis combining quantitative profiling of gdh, model batch fermentations, microbiota manipulation, and kinetic modelling of acrolein formation. Our results suggest that GDH activity is a common trait of intestinal microbiota shared by a few taxa, which was dependent on overall gdh abundance. Anaerobutyricum hallii was identified as a key taxon in GDH metabolism, and its supplementation increased the rate of GDH activity and acrolein release, which enhanced the transformation of HCA and reduced fermentation activity. The findings of this first systematic study on acrolein release by intestinal microbiota indicate that dietary and microbial modulation might impact GDH activity, which may influence host health.